Expression of an extremophilic xylanase in Nicotiana benthamiana and its use for the production of prebiotic xylooligosaccharides - David Talens-Perales; María Nicolau-Sanus; Julio Polaina; José-Antonio Daròs (Scientific Reports, 2022)
Abstract A gene construct encoding a xylanase, which is active in extreme conditions of temperature and alkaline pH (90 °C, pH 10.5), has been transitorily expressed with high efficiency in Nicotiana benthamiana using a viral vector. The enzyme, targeted to the apoplast, accumulates in large amounts in plant tissues in as little as 7 days after inoculation, without detrimental effects on plant growth. The properties of the protein produced by the plant, in terms of resistance to temperature, pH, and enzymatic activity, are equivalent to those observed when Escherichia coli is used as a host. Purification of the plant-produced recombinant xylanase is facilitated by exporting the protein to the apoplastic space. The production of this xylanase by N. benthamiana, which avoids the hindrances derived from the use of E. coli, namely, intracellular production requiring subsequent purification, represents an important step for potential applications in the food industry in which more sustainable and green products are continuously demanded. As an example, the use of the enzyme producing prebiotic xylooligosdaccharides from xylan is here reported.